Cardiogenic shock teams and centres: a contemporary review of multidisciplinary care for cardiogenic shock - Moghaddam, Nima; Diepen, Sean; So, Derek; Lawler, Patrick R.; Fordyce, Christopher B. (ESC Heart Failure, 2021)
Cardiogenic shock (CS) portends high morbidity and mortality in the contemporary era. Despite advances in temporary mechanical circulatory supports (MCS), their routine use in CS to improve outcomes has not been established. Delays in diagnosis and timely delivery of care, disparities in accessing adjunct therapies such revascularization or MCS, and lack of a systematic approach to care of CS contribute to the poor outcomes observed in CS patients. There is growing interest for developing a standardized multidisciplinary team‐based approach in the management of CS. Recent prospective studies have shown feasibility of CS teams in improving survival across a spectrum of CS presentations. Herein, we will review the rationale for CS teams focusing on evidence supporting its use in streamlining care, optimizing revascularization strategies, and patient identification and MCS selection. The proposed structure and flow of CS teams will be outlined. An in‐depth analysis of four recent studies demonstrating improved outcomes with CS teams is presented. Finally, we will explore potential implementation hurdles and future directions in refining and widespread implementation of dedicated cross‐specialty CS teams.